2015
DOI: 10.1117/1.jbo.20.3.037001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive, real-time analysis of biomarkers in breath using tunable external cavity laser and off-axis cavity-enhanced absorption spectroscopy

Abstract: A robust biomedical sensor for ultrasensitive detection of biomarkers in breath based on a tunable external cavity laser (ECL) and an off-axis cavity-enhanced absorption spectroscopy (OA-CEAS) using an amplitude stabilizer is developed. A single-mode, narrow-linewidth, tunable ECL is demonstrated. A broadly coarse wavelength tuning range of 720 cm⁻¹ for the spectral range between 6890 and 6170 cm⁻¹ is achieved by rotating the diffraction grating forming a Littrow-type external-cavity configuration. A mode-hop-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…To determine the line strength S, the integrated CEAS signal is plotted as a function of the pressure in our previous work. 19 The slope of the linear fit through the data points gives a value for S of 2.5 × 10 −21 cm −1 ∕molecule cm −2 , which is in agreement with the result reported by Webber et al 21 In our earlier work, the integrated absorption ½ðI 0 ∕IÞ − 1∕d is also plotted as function of the NH 3 concentration, on the basis of Eq. (1).…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…To determine the line strength S, the integrated CEAS signal is plotted as a function of the pressure in our previous work. 19 The slope of the linear fit through the data points gives a value for S of 2.5 × 10 −21 cm −1 ∕molecule cm −2 , which is in agreement with the result reported by Webber et al 21 In our earlier work, the integrated absorption ½ðI 0 ∕IÞ − 1∕d is also plotted as function of the NH 3 concentration, on the basis of Eq. (1).…”
Section: Methodssupporting
confidence: 90%
“…1). 19,20 Briefly, a broadly coarse wavelength tuning range of 170 nm (720 cm −1 ) for the spectral range between 1451 and 1621 nm is achieved by rotating the diffraction grating forming ECL configuration in single-mode operation. A mode-hop-free tuning range of 1.85 cm −1 is obtained.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the levels of carbon dioxide, we used our home‐made ECL‐based OA‐CEAS setup (Bayrakli and Akman, ; Bayrakli, ). In our recently published work (Bayrakli and Akman, ) it was shown that our CEAS system is able to detect any molecules in breath at concentrations to the ppbv range that have suitable absorption lines in the spectral range between 1450 and 1620 nm.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the levels of carbon dioxide, we used our home‐made ECL‐based OA‐CEAS setup (Bayrakli and Akman, ; Bayrakli, ). In our recently published work (Bayrakli and Akman, ) it was shown that our CEAS system is able to detect any molecules in breath at concentrations to the ppbv range that have suitable absorption lines in the spectral range between 1450 and 1620 nm. This setup is based on a wide wavelength‐tunable (170 nm, 720 cm −1 ), narrow‐linewidth (<140 kHz), single‐mode ECL operated at around 1550 nm in Littrow configuration and a high‐finesse CEAS cell formed by two highly reflective mirrors positioned 50 cm apart with a reflectivity of >99.96% over a spectral range of 700–1650 nm with a 2.54 cm diameter and a radius of curvature of 1 m (LayerTec GmbH; Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…They found that the linewidths are little affected by the presence of an AR coating on the diode facet and that the grating resolution has a larger effect on the linewidth than the grating reflectivity. 38 The laser linewidth can be determined using several methods, such as optical cavity measurements, 29 heterodyne measurements, 37 homodyne/heterodyne interferometry using a long interferometer delay, 39 measurements from the frequency noise power spectral density, 40 measurements from root-meansquare frequency deviation, 41 and saturation spectroscopy. 42 Tkach and Chraplyvy 43 reported that there are five distinct regimes of feedback effects, with well-defined transitions between them as a function of feedback power ratio.…”
Section: Linewidthmentioning
confidence: 99%